2013
DOI: 10.1002/cncr.28057
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregiving for cancer patients

Abstract: According to the recent worldwide estimation by the GLOBOCAN project, in total, 12.7 million new cancer cases and 7.6 million cancer deaths occurred in 2008. The worldwide number of cancer survivors within 5 years of diagnosis has been estimated at be almost 28.8 million. Informal caregivers, such as family members and close friends, provide essential support to cancer patients. The authors of this report provide an overview of issues in the study of informal caregivers for cancer patients and long-term surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
140
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 54 publications
6
140
0
3
Order By: Relevance
“…Several researches from around the world have been conducted on family caregivers of cancer patients in the terminal phase, suggesting that their common problems include depression (7), financial pressure, low quality of life, cessation of work and running out of financial savings (8), grief and anxiety (9). There are certain ethnic, racial, value-related, cultural belief-based and family system characteristics, which might cause the caregivers of different countries to experience their role differently (10), and according to the knowledge of the researcher, up to now in Iran, no reliable research has been conducted on family caregivers of cancer patients in the terminal phase and in accordance with care conditions in the country. By considering the difference of psychological pressure sources according to treatment stages for cancer (11), the present qualitative research has been conducted by the aim of gaining a deep understanding of the experiences of family caregivers and consequences of taking care of cancer patients in terminal phase in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches from around the world have been conducted on family caregivers of cancer patients in the terminal phase, suggesting that their common problems include depression (7), financial pressure, low quality of life, cessation of work and running out of financial savings (8), grief and anxiety (9). There are certain ethnic, racial, value-related, cultural belief-based and family system characteristics, which might cause the caregivers of different countries to experience their role differently (10), and according to the knowledge of the researcher, up to now in Iran, no reliable research has been conducted on family caregivers of cancer patients in the terminal phase and in accordance with care conditions in the country. By considering the difference of psychological pressure sources according to treatment stages for cancer (11), the present qualitative research has been conducted by the aim of gaining a deep understanding of the experiences of family caregivers and consequences of taking care of cancer patients in terminal phase in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…As the number of cancer patients increases, new treatments methods are developed, symptoms are controlled, and psychological and physiological quality is improved; however, patients are directed to home care due to the lack of staff, accommodations and economic difficulties (Bektas and Akdemir, 2006;Romito et al, 2013). Home care has gradually gained more importance and it is a great burden on the shoulders of caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the role of the caregiver does not always emerge from the real desire to accept this responsibility: values, beliefs, ethnicities, and family systems are related to this choice however the caregiver is a member of the extended or nuclear family that takes on the moral duty of care. 17 In this study, it was found that the concern with the loved one emanates not only from family ties, but, above all, from the commitment that caregivers imposed on themselves, the obligation to care and be with the other during the course of the disease.…”
Section: Discussionmentioning
confidence: 81%